The Chromosomal and Functional Clustering of Markedly Divergent Human-Mouse Orthologs Run Parallel to their Compositional Features - A. Fuertes Miguel; R. Rodrigo José; Zuckerkandl Emile; Alonso Carlos (Journal of DNA And RNA Research, 2016)
It was, previously, reported that the specific pattern of the compositional features of particular human-mouse orthologs defining in human two clusters, named C2 and C5, are present in different clusters in mouse. Since, thus, these orthologs can harbor a significant number of nucleotide differences a large sample of human-mouse orthologs having in human the C2 and C5 compositional features were collected in order to identify the orthologs that have been conserved or diverged during speciation. From the collection, 945 and 1051 orthologs had in human the C2 and C5 profile, respectively, while in mouse only 77 and 125, respectively, had these profiles. We further analyzed whether or not the frequency-usage of trinucleotides having the same gross composition computed from the reading of all nearest-neighbors of the DNA sequence might convey a layer of biological information in terms of chromosomal topology and function. In human, more than 50% of the C2 and C5 genes were found distributed in six chromosomes and preferentially located in GC-rich bands of chromosomes 11, 16 and 19. It was, also, found that 80% of the entire set of genes of band 19p13.3 had the C2 and C5 profile. The data shown also indicate that the proteins codified by the C5 genes have a bias towards nucleus and cytoplasm and specific post-translational modifications while the proteins codified by the C2 genes are mainly located in the cellular membrane or secreted to the external cellular milieu and particular post-transcriptional modifications
Keywords: gene clustering